"Queering" Spiritual Direction: Towards a Trans*-Literary Praxis 1. Issue 3 (September 2014) - Mann, Rachel
<x content-type="archive" xml:space="preserve">Abstract</x> The praxis of spiritual direction has a number of well-established orthodoxies, most notably Ignatian, Franciscan and Benedictine, each typically characterized as paths that invite us to become our "true" selves in God. This article interrogates practices of spiritual direction from a queer perspective, examining the exclusions and inclusions for trans* people implicit in traditional notions of "spiritual direction". Concentrating on a theo-literary reading of Psalm 139 using trans* understandings of the terms "passing" and "stealth" and grounded in my experience as a trans* woman, a spiritual director and poet, this article presents critical strategies to enable trans* Christians to locate themselves in the Christian spiritual discourse.